OA03-RF01.07. Neoadjuvant Chemoimmunotherapy Versus Upfront Surgery for Clinical T2N0 Esophageal Squamous Cell Carcinoma: A Propensity Score-Matched Analysis - Xu Huang; Zitao Jian; Wenyi Xu; Runze You; Han Tang; Lijie Tan (Diseases of the Esophagus, 2026)
Abstract Topic Esophageal Cancer: Adjuvant and Neo-Adjuvant Therapies Background The role of neoadjuvant chemoimmunotherapy (nICT) in clinical T2N0 (cT2N0) esophageal squamous cell carcinoma (ESCC) remains controversial. Current guidelines recommend upfront surgery for this population, yet clinical staging inaccuracy frequently results in pathological understaging at surgery. This study aimed to evaluate the efficacy and oncological outcomes of nICT compared with upfront surgery in patients with cT2N0 ESCC. Methods We conducted a multicenter retrospective cohort study of 643 patients with cT2N0 ESCC treated between July 2016 and June 2025 at four institutions: Zhongshan Hospital of Fudan University, Zhongshan Hospital Center of Geriatric Medicine, Zhongshan Hospital Xiamen Branch, and Lu’an Affiliated Hospital of Anhui Medical University. Patients received either nICT followed by surgery (nICT group, n = 112) or upfront surgery alone (Surgery group, n = 651). Propensity score matching (PSM) at a 1:1 ratio was performed adjusting for age, sex, body mass index, comorbidities, ECOG performance status, and tumor location, yielding 112 matched pairs (N = 224). The primary endpoints were disease-free survival (DFS) and overall survival (OS). Pathological response was assessed in the nICT group using tumor regression grade (TRG). Results After PSM (112 pairs, N = 224), baseline characteristics were well balanced between groups (all SMD < 0.1). At a median follow-up of 41.8 months, nICT was associated with significantly improved DFS (HR = 0.556, 95% CI 0.360–0.859, P = 0.007) and OS (HR = 0.440, 95% CI 0.237–0.818, P = 0.008) compared with upfront surgery. The 3-year DFS rate was 70.8% in the nICT group versus 49.3% in the Surgery group, and 3-year OS rate was 86.7% versus 80.2%, respectively (Figure 1). In the nICT group, pCR was achieved in 26.8% (30/112), MPR in 60.7% (68/112), and T-downstaging in 63.4% (71/112) of patients; effective tumor regression (TRG 1–3) was observed in 88.4% (Figure 2). Notably, among surgery-alone patients, only 28.1% were correctly staged at final pathology, with 54.9% understaged and 45.5% harboring unexpected nodal metastasis, which was associated with significantly worse survival. Conclusion Neoadjuvant chemoimmunotherapy significantly improved DFS and OS compared with upfront surgery in patients with cT2N0 ESCC. The high clinical understaging rate observed in the surgery-alone group suggests that a substantial proportion of cT2N0 patients harbor occult advanced disease that benefits from neoadjuvant treatment. These findings from this multicenter analysis support extending the indication of neoadjuvant chemoimmunotherapy to cT2N0 ESCC.